Efektivitas Pendekatan STEM Berbasis Collaborative Learning terhadap Pemahaman Konsep Abstrak Siswa Sekolah Dasar - Syarifuddin Syarifuddin; Ika Wirahmad; Mikrayanti Mikrayanti (Bima Journal of Elementary Education, 2025)
Understanding abstract concepts is still a major challenge in learning science and mathematics at the elementary school level. This study aims to test the effectiveness of a STEM-based Collaborative Learning approach to improving students' understanding of abstract concepts. This study used a quasi-experimental method with a one-group pretest-posttest design, involving 25 fifth-grade students from an elementary school in Jakarta who were selected through purposive sampling. The research instruments consisted of abstract concept comprehension tests (pretest and posttest), collaborative involvement observation sheets, and student participation questionnaires. Data analysis was carried out quantitatively using a paired sample t-test and supported by thematic qualitative analysis. The results showed that there was a significant increase in the abstract concept comprehension score, with an average pretest score of 62.2 increasing to 75.9 on the posttest. The t-test results obtained a value of t = -45.0 with p <0.001, which indicates the statistical effectiveness of the intervention. Observations and questionnaires showed high student involvement in group discussions and collaborative application of concepts. The conclusion of this study is that STEM-based Collaborative Learning is able to facilitate the learning of abstract concepts in a more meaningful and participatory way. Suggestions for further research are to test the effectiveness of this approach at different levels and to explore its integration with digital technology to strengthen students' absorption of abstract, cross-disciplinary material.